Trust aware energy management system for smart homes appliances. (January 2022) - Qureshi, Kashif Naseer; Alhudhaif, Adi; Hussain, Adil; Iqbal, Saleem; Jeon, Gwanggil
Abstract: Smart grids have gained popularity to manage energy resources on the consumption side. Energy management on the home side is still under consideration where the system controls the home appliances intelligently with cost-effective and manageable processes. This paper presents a Trust-aware Energy Management System for Smart Homes (TEMSH) by using smart scheduling and time management based on controllable and uncontrollable appliances management. This system is based on advanced communication technologies and security mechanisms. The trust mechanism provides the authentication services at the edge level to secure the user data from any type of unauthorized access and data leakage. The proposed system is deployed on houses to analyze the overall energy consumption and appliances. The results indicate the proposed system is more feasible for home appliances and able to manage and reduce the energy cost by around 55% cumulative Cost in the shape of bills and best for a green environment. The proposed system will be feasible to control the energy crises all over the world and reduce energy utilization and cost at the home level. Graphical abstract: Image, graphical abstract This paper presents a Trust-aware Energy Management System for Smart Homes (TEMSH) by using smart scheduling and time management based on controllable and uncontrollable appliances management. This system is based on advanced communication technologies and security mechanisms. The trust mechanism provides the authentication services at the edge level to secure the user data from any type of unauthorized access and data leakage. The proposed system is deployed on houses to analyze the overall energy consumption and appliances.